2017
DOI: 10.1016/j.ijscr.2017.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic extraction of a giant peritoneal loose body: Case report and review of literature

Abstract: HighlightsLaparoscopic extraction of a giant peritoneal loose body is a good adaption, even if with no symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…However, the resulting compression of the surrounding organs can lead to mild clinical manifestations, including abdominal pain, intestinal obstruction, urinary retention, and frequent urination. 2,3 Very few cases of GPLB have been reported worldwide. Given that most GPLBs probably remain undetected throughout the patient's life, it is difficult to estimate the probability of its occurrence and it is unlikely to be prevented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the resulting compression of the surrounding organs can lead to mild clinical manifestations, including abdominal pain, intestinal obstruction, urinary retention, and frequent urination. 2,3 Very few cases of GPLB have been reported worldwide. Given that most GPLBs probably remain undetected throughout the patient's life, it is difficult to estimate the probability of its occurrence and it is unlikely to be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…However, the resulting compression of the surrounding organs can lead to mild clinical manifestations, including abdominal pain, intestinal obstruction, urinary retention, and frequent urination. 2 , 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact origin of peritoneal loose bodies is unknown, but many authors suggest that they form from a detached appendix epiploicae secondary to torsion and ischemia followed by saponification, calcification, and fibrosis, with gradual increase in size as a result of albumin accumulation from exudative peritoneal fluid [ 4 , 3 ]. It was also reported that giant peritoneal bodies in females can arise from auto-amputated adnexa or a uterine leiomyoma [ 5 ]. Rarely, peritoneal bodies receives blood supply from attachment to the surrounding omentum (a parasitized peritoneal body) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the frequency of indeterminate differentials following imaging for PBLs, we focused on the development of a simple algorithm to identify these rare manifestations ( Fig. 5 ) [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Based on the literature review, MRI early in the diagnostic pathway is beneficial.…”
Section: Literature Reviewmentioning
confidence: 99%